Answer: x = 3
Explanation:
2(3x-5)=8
first, you multiply 2 by 3x and -5.
6x-10=8
since we want 6x by it’s self we add 10 to its self and add it to 8 as well.
6x = 18
now we divide 6 to both 6x and 18.
x = 3
hope this helped
Answer:
Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :
2*(3*x-5)-(8)=0
2 • (3x - 5) - 8 = 0
Pull out like factors :
6x - 18 = 6 • (x - 3)
6 • (x - 3) = 0
Solve : 6 = 0
Add 3 to both sides of the equation :
5.7m questions
7.5m answers